EVALUATING THE IMPACT OF SERVICE OFFERINGS ON CUSTOMER SATISFACTION IN SUPERMARKETS: A STUDY OF NAGPUR CITY - Gurupanch, Hariram Dasharath; Dixit, Chandrahas Arunrao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Supermarkets and the retail sector as a whole provide a wide variety of services that are essential to meeting the demands of consumers. The purpose of this research is to look at how happy customers are in Nagpur City in regard to the variety of services offered by supermarkets. Using surveys to gather primary data from shoppers in supermarkets, this study takes a quantitative approach. Customers' opinions on our service offerings, including our product selection, billing efficiency, personnel support, home delivery, reward programs, and general shopping experience, were evaluated using a structured questionnaire. This research compares two hypotheses: one holds that the variety of services provided has no bearing on customers' happiness, while the other holds that this is not the case. Statistical methods, such as correlation and regression analysis, are used to determine how different aspects of the service affect the satisfaction levels of the customers. Supermarkets can use the results to improve their service methods and better understand their customers' preferences. This study has real-world consequences for grocery store owners and managers in Nagpur City and adds to the body of knowledge on retail management and customer service.